DOMESTIC VIOLENCE ACCORDING TO LAW NUMBER 23 OF 2004: A JURIDICAL STUDY - Hadi Purnomo (Fox Justi : Jurnal Ilmu Hukum, 2023)
Domestic violence (KDRT) is a social problem that is detrimental, violates human rights, and has a serious impact on the welfare of individuals and society. This research aims to conduct a juridical study of the implementation of Law Number 23 of 2004 concerning the Elimination of Domestic Violence in Indonesia. The research method used is a descriptive analytical method with a normative juridical approach. Data was obtained through literature study, analysis of the content of laws, and study of documentation related to government policies. The research results show that Law Number 23 of 2004 has become an important legal basis for efforts to eradicate domestic violence in Indonesia. The research results show that Law Number 23 of 2004 concerning the Elimination of Domestic Violence (UU PKDRT) is a significant step in handling cases of domestic violence in Indonesia. This law provides clear definitions of various forms of violence and identifies who is included in the domestic sphere. The importance of this law can be seen in the effort to provide legal protection to victims, especially women, and change society's paradigm towards domestic violence. In addition, the Domestic Violence Law creates a legal basis for addressing inequality, opening wider access to justice, and identifying actors involved in violence, such as domestic workers. The research conclusion confirms that the PKDRT Law is not only a legal instrument, but also a tool for fairer social change and the protection of human rights.